Book Reviews - Kneeshaw, Stephen; Harvey, Richard; Campbell, D'Ann; Dubay, Robert W.; Reilly, John T.; Marran, James F.; Ellis, Ann W.; Lewis, Thomas T.; Barnes, Howard A.; Schubart, Richard D.; Selcer, Richard; Kriegel, Abraham D.; et al. (Teaching History: A Journal of Methods, 2020)
Robert William Fogel and G. R. Elton. Which Road to the Past? Two Views of History. New Haven and London: Yale University Press, 1983. Pp. vii, 136. Cloth, $14.95. Review by Stephen Kneeshaw of The School of the Ozarks. Emmanuel LeRoy Ladurie. The Mind and Method of the Historian. Translated by Sian Reynolds and Ben Reynolds. Chicago: University of Chicago Press, 1981. Pp. v, 310. Paper, $9.95. Review by Richard Harvey of Ohio University. John E. O'Connor, ed. American History/ American Television: Interpreting the Video Past. New York: Frederick Ungar Publishing Company, 1983. Pp. 463. Cloth, $17.50; Paper, $8.95. Review by D' Ann Campbell of Indiana University. Foster Rhea Dulles & Melvyn Dubofsky. Labor in America: A History. Arlington Heights, Illinois: Harlan Davidson, Inc., 1984. 4th edition. Pp. ix, 425. Cloth, $25.95. Paper, $15.95. Review by Robert W. Dubay of Bainbridge Junior College. Karen Ordahl Kupperman. Roanoke: The Abandoned Colony. Totowa, New Jersey: Rowman & Allanheld, 1984. Pp. viii, 182. Cloth, $24.95; Paper, $12.50. Review by John T. Reilly of Mount Saint Mary College. Kevin O'Reilly. Critical Thinking in American History: Exploration to Constitution. South Hamilton, Massachusetts: Hamilton-Wenham Regional High School, 1983. Pp. 86. Paper, $2.95. Teacher's Guides: Pp. 180. Paper, $12.95; Kevin O'Reilly. Critical Thinking in American History: New Republic to Civil War. South Hamilton, Massachusetts: Hamilton-Wenham Regional High School, 1984. Pp. 106. Paper, $2.95. Teacher's Guide: Pp. 190. Paper, $12.95. Review by James F. Marran of New Trier Township High School, Winnetka, Illinois. Michael J. Cassity, ed. Chains of Fear: American Race Relations Since Reconstruction. Westport, Connecticut: Greenwood Press, 1984. Pp. xxxv, 253. Cloth, $35.00. Review by Ann W. Ellis of Kennesaw College. L. P. Morris. Eastern Europe Since 1945. London and Exeter, New Hampshire: Heinemann Educational Books, 1984. Pp. 211. Paper, $10.00. Review by Thomas T. Lewis, Mount Senario College. John Marks. Science and the Making of the Modern World. Portsmouth, New Hampshire: Heinemann Educational Books, Inc., 1983. Pp. xii, 507. Paper, $25.00. Review by Howard A. Barnes of Winston-Salem State University. Kenneth G. Alfers, Cecil Larry Pool, William F. Mugleston, eds. American's Second Century: Topical Readings, 1865-Present. Dubuque, Iowa: Kendall/ Hunt Publishing Co., 1984. Pp. viii, 381. Paper, $8.95. Review by Richard D. Schubart of Phillips Exeter Academy. Sam C. Sarkesian. America's Forgotten Wars: The Counterrevoltuionary Past and Lessons for the Future. Westport, Connecticut: Greenwood Press, 1984. Pp. xiv, 265. Cloth, $29.95. Review by Richard Selcer of Mountain View College. Edward Wagenknecht. Daughters of the Covenant: Portraits of Six Jewish Women. Amherst: University of Massachusetts, 1983. Pp. viii, 192. Cloth, $17.50. Review by Abraham D. Kriegel of Memphis State University. Morton Borden. Jews, Turks, and Infidels. Chapel Hill and London: University of North Carolina Press, 1984. Pp. x, 163. Cloth, $17.95. Review by Raymond J. Jirran of Thomas Nelson Community College. Richard Schlatter, ed. Recent Views on British History: Essays on Historical Writing Since 1966. New Brunswick: Rutgers University Press, 1984. Pp. xiii, 524. Cloth, $50.00. Review by Fred R. van Hartesveldt of Fort Valley State College. Simon Hornblower. The Greek World, 479-323 B.C. London and New York: Methuen, 1983. Pp. xi, 354. Cloth, $24.00; Paper, $11.95. Review by Dan Levinson of Thayer Academy, Braintree, Massachusetts. H. R. Kedward. Resistance in Vichy France. New York: Oxford University Press, 1978. Paper edition 1983. Pp. ix, 311. Paper, $13.95. Review by Sanford J. Gutman of the State University of New York at Cortland.